2019
DOI: 10.3389/fimmu.2019.01796
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Genetic Findings for Precision Medicine in Vasculitis

Abstract: Vasculitides are a heterogeneous group of low frequent disorders, mainly characterized by the inflammation of blood vessels that narrows or occlude the lumen and limits the blood flow, leading eventually to significant tissue and organ damage. These disorders are classified depending on the size of the affected blood vessels in large, medium, and small vessel vasculitis. Currently, it is known that these syndromes show a complex etiology in which both environmental and genetic factors play a major role in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 148 publications
(173 reference statements)
0
8
0
Order By: Relevance
“…Antigen specificity is determined by specific pockets in the antigen-binding groove of the HLA molecule, and therefore the amino acid sequence of these pockets is crucial to understanding the risk for certain autoimmune diseases ( 35 ). While the MHC constitutes the strongest association in vasculitis, there are several loci outside the MHC, including SERPINA1, PRTN3, SEMA6A, PTPN22, CTLA4, FCGR3B , and ARPC1B that have also been established as genetic risk factors for these diseases, coding for immunological molecules that increase susceptibility to autoimmunity ( 36 ) ( Table 1 ).…”
Section: Genetic Variants and Their Association With Immunopathogenesis In Vasculitismentioning
confidence: 99%
See 2 more Smart Citations
“…Antigen specificity is determined by specific pockets in the antigen-binding groove of the HLA molecule, and therefore the amino acid sequence of these pockets is crucial to understanding the risk for certain autoimmune diseases ( 35 ). While the MHC constitutes the strongest association in vasculitis, there are several loci outside the MHC, including SERPINA1, PRTN3, SEMA6A, PTPN22, CTLA4, FCGR3B , and ARPC1B that have also been established as genetic risk factors for these diseases, coding for immunological molecules that increase susceptibility to autoimmunity ( 36 ) ( Table 1 ).…”
Section: Genetic Variants and Their Association With Immunopathogenesis In Vasculitismentioning
confidence: 99%
“…Currently, there is not much literature on the genetic factors that contribute to CSVV pathogenesis. However, some have suggested that the gene ARPC1B may play a role in predisposition to this disease ( 36 , 37 ). The ARPC1B gene encodes ARPC1B, which is an isoform of ARPC1 (actin-related protein complex-1) and one of the regulatory subunits of the Arp2/3 complex involved in actin polymerization and cellular motility ( 35 ).…”
Section: Genetic Variants and Their Association With Immunopathogenesis In Vasculitismentioning
confidence: 99%
See 1 more Smart Citation
“…A study at Boston University showed that athletes who had TMEM106B gene in their brain were highly reactive to inflammation. The genetic risk factors of vasculitis depend on the type of condition; for example, in Takayasu arteritis, HLA (human leukocyte antigen) region occurs as the leading risk factor [16].…”
Section: Genetics Of the Diseasementioning
confidence: 99%
“…Both PLG and P4HA2 play a role in the regulation of angiogenesis and vascular remodeling. The plasminogen system is known to regulate several pathways possibly related to the GCA pathogenesis, such as lymphocyte recruitment and production of TNF-α and IL-6 cytokines (96,97). The P4HA2 gene is a hypoxia-responsive gene with a role in collagen biosynthesis and composition of ECM.…”
Section: Giant Cell Arteritis (Gca)mentioning
confidence: 99%